Adsorption of rhodamine B by solid pineapple waste - Shamsuddin Chik Zi, 1989-; Rahmalan Ahamad, supervisor; fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011